2020
DOI: 10.1186/s13014-020-01521-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined radiotherapy and concurrent tumor treating fields (TTFields) for glioblastoma: Dosimetric consequences on non-coplanar IMRT as initial results from a phase I trial

Abstract: Background: Glioblastoma is a rapidly proliferating tumor. Patients bear an inferior prognosis with a median survival time of 14-16 months. Proliferation and repopulation are a major resistance promoting factor for conventionally fractionated radiotherapy. Tumor-Treating-Fields (TTFields) are an antimitotic modality applying low-intensity (1-3 V/ cm), intermediate-frequency (100-300 kHz) alternating electric-fields. More recently interference of TTFields with DNAdamage-repair and synergistic effects with radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 33 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…The secondary endpoint of the trial is the dosimetric skin exposure. A previous study from our group showed that in the first seven patients included in the PriCoTTF‐phase I/II trial dose deviations in the CTV due to transducer arrays were not clinically significant confirming feasibility of combined adjuvant radiochemotherapy and concurrent TTFields from a dosimetric point of view 9 . The dose buildup in the skin resulted in a dose increase of below 8.5% outside the “hottest” 1 cm 2 with TTFields which moved around their center position 9 .…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…The secondary endpoint of the trial is the dosimetric skin exposure. A previous study from our group showed that in the first seven patients included in the PriCoTTF‐phase I/II trial dose deviations in the CTV due to transducer arrays were not clinically significant confirming feasibility of combined adjuvant radiochemotherapy and concurrent TTFields from a dosimetric point of view 9 . The dose buildup in the skin resulted in a dose increase of below 8.5% outside the “hottest” 1 cm 2 with TTFields which moved around their center position 9 .…”
Section: Introductionmentioning
confidence: 73%
“…1 cm, at each change of the transducer arrays in the plane of the skin. This variation of TTField array position from fixation period to fixation period resulted in 95% confidence ellipses with a mean half‐length of the major axis of about 2.7 cm and of the minor axis of about 1.8 cm 9 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to traditional chemotherapy and radiation, there are also a number of innovative treatments that have come into recent use for GBM, including carmustine wafers (Gliadel®) [9,10] , an intracranially implanted local chemotherapy, as well as low-intensity alternating electrical tumor treating fields (Optune® therapy) with anti-proliferative properties [11][12][13][14] . These treatment options have been shown to confer significant benefit to some patients and have the advantage of being well-tolerated with few side effects as they are localized (Gliadel®) or non-invasive (Optune®) therapies [9][10][11][12][13][14] . Tumor treating fields (TTFields) in particular show true potential for incorporation into standard-of-care based on a recent clinical trial of TTFields plus TMZ, which produced a median overall survival of 20.9 months compared to TMZ alone [14,15] .…”
Section: Introductionmentioning
confidence: 99%